PENERAPAN MODEL KOOPERATIF TIPE THINK PAIR SHARE BERBASIS KONTEKS TAMAN OLAHRAGA MEGANG PADA PEMBELAJARAN MATEMATIKA DI KELAS VII SMPN 8 LUBUKLINGGAU - Elia Fitriani; Sukasno; Drajat Friansah (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2025)
Mathematics is a fundamental science that plays an important role in everyday life. However, students' learning outcomes in this subject are still relatively low because the learning process is still dominated by conventional methods, which tend to make students feel bored and less interested. To overcome this problem, it is necessary to implement a more active learning model, in which students take on the primary role in the learning process, while the teacher acts as a facilitator. This study aims to determine the mastery of mathematics learning outcomes of seventh-grade students at SMPN 8 Lubuklinggau after participating in the cooperative learning model of Think Pair Share (TPS). The population consists of all seventh-grade students at SMPN 8 Lubuklinggau in the 2024/2025 academic year, totaling 224 students, with a sample of 32 students from class VII F. Data collection was conducted using a test technique in the form of four essay questions. The results of the t-test analysis showed that = 2,5 dan = 1,6955 (> ). Thus, it can be concluded that the average mathematics learning outcomes of seventh-grade students at SMPN 8 Lubuklinggau after participating in the Think Pair Share cooperative learning model are significantly complete. The students' average score was 72, with a mastery level reaching 78%..